Predictors of Crowd Effect in Football: Evidence From Five Major Football Leagues of Europe - Abdullah Yiğit Güngör; Tuncer Gövdeli (Türk Spor ve Egzersiz Dergisi, 2022)
This study aims to determine predictors of crowd effect in five major football leagues in Europe. Literature review shows that crowd effect can be determined as size, proximity or density for the analysis. In this study, density was selected among them. Therefore, stadium occupancy rates were used as the crowd effect indicator. As the predictors of crowd effect; total transfer expenditure, total market value, average goals scored per match, UEFA coefficients of each league were utilized as variables of the research. In addition, gross domestic product of each country were included in the analysis as the predictor. Because supporters’ economic conditions are also important to afford ticket prices. In this context, data regarding the variables includes from the season of 2005-2006 to 2019-2020 for English Premier League, French Ligue 1, German Bundesliga, Italian Serie A, Spanish La Liga. In this study, panel data analysis was used among quantitative research methods. Stationary of data was determined at the level of I(1). It was indicated through cointegration test that there was a cointegration relationship in the panel. Hence, stadium occupancy rate would move together with other variables in the long term except total market value. According to panel causality analysis results; total transfer expenditure, average goals scored per match, and UEFA coefficients, and gross domestic product are predictors of stadium occupancy rate.